Stapled trans-anal rectal resection for the surgical management of obstructed defecation syndrome: our experience in Bangladesh (BIRDEM Medical Journal, 2020)
Background: Obstructed defecation syndrome (ODS) is one of the commonest constipation related disorders confronted by surgeons in Bangladesh. Stapled transanal rectal resection (STARR) is a novel surgical technique specific for ODS. This study was designed to evaluate the effectiveness of STARR on patients with ODS in Bangladesh.Methods: Thirty (30) female patients (age: 46±13.2 years) with ODS, were selected for this observational study, from July 2016 to July 2019, in a private hospital of Dhaka. Patients were interviewed with standardized questionnaire at study enrolment and up to 3 months postoperatively. Surgical outcome was quantified according to the Longo’s Modified ODS score (MODS).Results: At initial consultation, the mean Longo’s MODS score was 17.6+1.9. Mean operative time was 39+6.2 minutes. Commonest complication was ‘staple line bleeding’ in 24(80%) patients intraoperatively & ‘defecatory urgency’ in 18(60 %) patients postoperatively. At postoperative 3-month follow-up, statistically significant (p